Strengthening Governance and Branding of Sharia Tourism Based on Local Wisdom among Tourism Stakeholders in Central Aceh Regency - Delfia Herwanis; Al Musanna; Rahayu Subakat; Elfi Rahmadhani; Ayu Rahmanengsi (Journal of Innovative and Creativity, 2026)
This community service initiative aims to strengthen governance and branding of Sharia tourism rooted in local wisdom among tourism stakeholders in Central Aceh Regency, Aceh Province, Indonesia. Central Aceh possesses significant tourism potential, including natural attractions, cultural heritage, and strong Islamic values embedded in Gayo local wisdom. However, limited managerial capacity, weak branding practices, and insufficient understanding of Sharia tourism concepts among tourism actors have hindered sustainable tourism development This program employed a participatory and capacity-building approach involving tourism stakeholders, community leaders, youth organizations, and local government representatives. The methods included needs assessment, workshops, focus group discussions, mentoring sessions, and program evaluation. The materials focused on Sharia tourism governance, Islamic-based service standards, integration of local wisdom, destination branding, and ethical digital marketing strategies. The results show an improvement in participants’ understanding and skills in implementing Sharia-compliant tourism governance, developing authentic destination branding based on Gayo culture, and utilizing digital media for promotion. Participants also demonstrated positive changes in service orientation, destination identity formulation, and collaborative management practices among tourism actors. In conclusion, this community service program contributes to the development of sustainable and ethical Sharia tourism while preserving local culture and Islamic values. The findings indicate that integrating Sharia principles with local wisdom enhances destination competitiveness and empowers local communities in regional tourism development.